Potential Of Biological Activities From Chemical Compounds Of Nigella Sativa As Anti-Osteoporosis, An Insilico Study - Mohammad Kuntadi Syamsul Hidayat (Journal of Global Pharma Technology, 2019)
Objective: The objective of the study was to investigate the potential of biological activities from chemical compounds of Nigella sativa (NS) as anti-osteoporosis using the computational chemistry insilico study. Methods: Database search from KnapSack was conducted to find out NS active compounds. Next, explore using the PASS Server database to find out compounds that have anti-osteoporosis potential. Exploration with STITCH to analyze the interaction of NS active compounds with cell proteins related to anti-osteoporosis, then docking using PyRx to determine the bond affinity that occurs between NS active compounds and cell proteins. Result: There were 36 active NS compounds, 28 of which had anti-osteoporosis potential. One active compound that has a probability to be active value (Pa)> 0.7 and 21 active compounds that have Pa: 0.3 - 0.7. Found 6 active compounds that have interactions and play a major role in the anti-osteoporosis process. With the docking process, binding affinity longifolene is obtained with estrogen receptors: -8.2 kcal / mol, compared to Bazedoxifene -9.6 kcal / mol Conclusion: From the study of insilico, Nigella sativa has the potential as an anti-osteoporosis Keywords : Osteoporosis, Nigella sativa, insilico, anti-osteoporosis